From Health in All Policies to Health for All Policies. (August 2022) - Greer, Scott L; Falkenbach, Michelle; Siciliani, Luigi; McKee, Martin; Wismar, Matthias; Figueras, Josep
Summary: Worldwide responses to the COVID-19 pandemic have shown that it is possible for politicians to come together across departmental boundaries. To this end, in many countries, heads of government and their health ministers work closely with all other ministries, departments, and sectors, including social affairs, internal affairs, foreign affairs, research and education, transport, agriculture, business, and state aid. In this Viewpoint, we build on the Health in All Policies approach by which the Sustainable Development Goals (SDGs) support intersectoral collaboration to promote health but argue that this relationship should be bidirectional and that health enables the attainment of other SDGs—Health for All Policies. We contend that strengthening health policies and improving health outcomes have major and tangible co-benefits for other sectors.